NILAIAN EKONOMI DAN PERSEPSI MASYAKARAT TERHADAP EKOSISTEM TERUMBU KARANG DI KOTA BONTANG - Saleha, Qoriah; Erwiantono, Erwiantono; Darmansyah, Oon; Sulistianto, Erwan (Jurnal Harpodon Borneo, 2017)
The aims of this research was to analyze the economic value and community’s perception toward coral reef ecosystem in Bontang City. The economic valuation analyzed used Contingen Value Method (CVM) using WTP and WTA approach, while the community’s perception analyzed used description method. The results showed that the total economic value was Rp 121.640.484,35 per hectare per year (which are the option value Rp 39.678.507,95 per hectare per year, the existence value Rp 40.762.578,19 per year per hectare, and the bequest value Rp 41.199.398,21 per year per hectare). Community’s perception consists of : (1) on the productivity of resources (100% respondents stated a decrease), (2) on the stability of the resources (50% stable, 50% unstable), (3) on the sustainability of resources (100% respondents stated very important)Keywords : economic valuation, perception, coral reef ecosystem, Bontang.